Partisipasi Politik Masyarakat Pada Pemilihan Umum Kepala Daerah dan Wakil Kepala Daerah di Kabupaten Katingan - Mambang Mambang; Rudi Rudi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
This study aims to find out, describe, and analyze the community's political participation in the Regional Head General Elections in Katingan Regency. The research method used is qualitative descriptive. The researcher wanted to describe the form of community political participation and the implementation of socialization in the general election of the Regional Head and Deputy Regional Head in Katingan District. Data sources are Katingan Regency KPU commissioner, Katingan Hilir PKK, and Community who have the right to vote in the Katingan Regency Election. Based on the results of the study it can be concluded that the community was very enthusiastic in participating in the campaign, but was less enthusiastic in giving voting rights. This condition is influenced by socio-economic conditions that cause transactional politics and still lack of public political awareness. Based on the results of this study, it was suggested that the Katingan Regency KPU together with the Katingan District Government continue to carry out socialization and political education for the community so that knowledge, political awareness, and political participation in the community increased. In addition, it should involve community leaders and religious leaders in the implementation of socialization and political education so that it is more effective and efficient, and it is expected that the active participation of the community to play an active role in the Katingan Regency election as a form of the five-year democratic party